The colorectal cancer immune paradox revisited. (1st February 2016) - Angelova, Mihaela; Charoentong, Pornpimol; Hackl, Hubert; Trajanoski, Z.
ABSTRACT: Tumor infiltrating lymphocytes (TILs) represent a strong independent predictor of relapse and overall survival in colorectal cancer (CRC). However, it appears that a majority of CRCs, i.e., microsatellite stable (MSS) tumors, are refractory to immune checkpoint blockers. The results of recent comprehensive analyses of genomic data provide possible answers.